Simplified Physically Based Model of Earthen Embankment Breaching - Wu, Weiming (Journal of hydraulic engineering (New York, N.Y.), 2013)
AbstractA simplified physically based model has been developed to simulate the breaching processes of homogenous and composite earthen embankments owing to overtopping and piping. The breach caused by overtopping flow is approximated as a flat broad-crested weir with a trapezoidal cross section, downstream connected with a vertical drop (headcut) and a straight slope for cohesive and noncohesive homogeneous embankments, respectively. For a composite dam with a clay core, the downstream becomes two straight slopes after the core is exposed. The breach by piping is assumed to be a flat pipe with rectangular cross section until the pipe top collapses and overtopping takes place. Sediment transport and morphology changes on the breach top flat section and downstream slopes and inside the pipe are calculated using a nonequilibrium total-load sediment transport model, whereas the time-averaged headcut migration rate is determined using an empirical formula. Stabilities of the side slope, pipe top, headcut, and clay core are analyzed by comparing the driving and resistance forces. The breach side slope is set as the average of the steepest stable slope and its corresponding failure plane angle. The model is able to handle dam and levee breaching by adopting various routing algorithms for headwater and tailwater levels and allowing embankment base erosion. It has been tested using 50 sets of data from laboratory experiments and field case studies. The calculated peak breach discharges, breach widths, and breach characteristic times agree generally well with the measured data.